Distributed leadership in a multicultural context : case study from Vietnam-Finland International School - Nguyen, Dieu (2020)
This study seeks to shed light on how distributed leadership is adopted and developed in a multicultural school context. Popular in the Western countries, i.e. the UK, distributed leadership has recently been introduced into Asian schools, especially the international ones, and faces both challenges and opportunities. Using the case of Vietnam-Finland International School (VFIS), the research looks into the perceptions of teachers and principals of distributed leadership, and how distributed leadership should be developed in this particular setting. Data was collected mainly via individual and group interviews, and essays at two different periods. Qualitative content analysis is applied. According to the findings, teachers and principals view distributed leader-ship from three aspects: leadership structure, leadership qualities and operational culture. Three challenges facing the development of distributed leadership are inappropriate decision-making involvement, complicated leadership structure, and lack of competent human resources. Cultural differences is the underlying force behind the first two challenges. Yet to develop distributed leadership is vital for a multicultural environment like VFIS. As a result, a new existence of distributed leadership emerges. To develop it is to build a clear organisational structure, a supportive organisational culture, teams, competent teachers, and multicultural leadership qualities. The study confirms the complexity of leadership context in international schools in Asia. It results in a new model of distributed leadership where hierarchical and distributive features are both present.